2010
DOI: 10.1098/rsta.2010.0211
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic hybrid systems for studying biochemical processes

Abstract: Many protein and mRNA species occur at low molecular counts within cells, and hence are subject to large stochastic fluctuations in copy numbers over time. Development of computationally tractable frameworks for modelling stochastic fluctuations in population counts is essential to understand how noise at the cellular level affects biological function and phenotype. We show that stochastic hybrid systems (SHSs) provide a convenient framework for modelling the time evolution of population counts of different ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 40 publications
0
97
0
1
Order By: Relevance
“…The review by Singh and Hespanha (2010) [31] shows some generalized approaches to model biochemical processes. For example Galpin et al (2008) [13] developed a modelling framework based on process algebra to describe the behaviour of hybrid biological systems.…”
Section: Intricate Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review by Singh and Hespanha (2010) [31] shows some generalized approaches to model biochemical processes. For example Galpin et al (2008) [13] developed a modelling framework based on process algebra to describe the behaviour of hybrid biological systems.…”
Section: Intricate Modelsmentioning
confidence: 99%
“…Reviews dedicated to some specific applications of hybrid models can also be found, for example in biological networks modelling [12], in cancer modelling [10,21,30,40], and more specifically tumour growth [24,29], tumour immunology [41], brain cancer [42] or angiogenesis [16]. Many special issues or reviews are also dedicated to the more specific field of hybrid systems [2,17,31,39] which can be considered as a subclass of hybrid models mainly (but not only) related to the field of automatic control.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples of such discontinuities are threshold-triggered firing in neurons (Izhikevich 2010), on-off switching of gene expression by a transcription factor (Imura et al 2010;Perkins et al 2010;Singh & Hespanha 2010), division in cells (Chen et al 2004;Battogtokh et al 2006;Osborne et al 2010) and certain types of chronotherapy for prostate cancer (Guo et al 2008;Ideta et al 2008;Shimada & Aihara 2008;Tanaka et al 2008Tanaka et al , 2010Hirata et al 2010;Suzuki et al 2010). Hence, the second aim of this Theme Issue is to discuss recent studies which apply hybrid dynamical systems to the fields of biology and medicine, through the nine articles with a variety of topics; this should stimulate applications of hybrid systems modelling to other research areas as well.…”
Section: Nonlinear Dynamics and Mathematical Modellingmentioning
confidence: 99%
“…A number of numerical methods have been developed to approximate the solution of the CME for more complex systems, including methods that approximate the CME by describing the probability distribution in terms of its moments. [4][5][6][7][8][9][10][11] When only the mean (the first moment) is taken into account, the moment expansion reduces to the MAK description. In the linear noise approximation (LNA), the CME is approximated by taking into account the mean (the first moment), and the variance and covariance (second central moments) of the distribution, whereby the second central moments are decoupled form the mean.…”
Section: Introductionmentioning
confidence: 99%